Surgical intermediate care unit: Concepts and experience on 300 patients - Henderson, Eduardo; Ruso, Luis; Alonso, Oscar; Ramos, Edgardo; Luchinsky, Alicia; Boudrandi, Sonia; Morelli, Raúl; Balboa, Oscar; Matteucci, Pablo; Praderi, Luis (Cirugía del Uruguay, 1994)
We present the experience on 300 consecutive patients, treated within a 20 months period (from ju/y 1988 to february 1990) in the Intermedia te Care Unit of the Surgical Clinic "F" of the Clinics Hospital in Montevideo. We define the concept of monovalent surgica/ unit: its assistance aims for the managment of high technical complexity proceedings, its value concerning education and research in the medica! and nursery areas. The occupation index of the unit was 59.3%. 48.4% of the cases were digestive cancers, acute abdomen disorders and politraumas; arterial, bife and pleuropulmonar diseases, 8%, 6. 7% and 5.6% respective/y; hydatidosis, 5%; and a disease group with a low incidence, 18.3%